2018
DOI: 10.1016/j.engfracmech.2018.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and fatigue behaviour of epoxy nanocomposites containing 1-D and 2-D nanoscale carbon fillers

Abstract: The present paper describes improvements in the fracture resistance of epoxy polymers due to the addition of either (a) one-dimensional (1-D) carbon nanofibres (CNFs), or (b) two-dimensional (2-D) graphene nanoplatelets (GNPs), or (c) hybrid combinations of these carbon nanofillers (i.e. using both CNFs and GNPs). The effects of the dimensional shape and concentration (i.e. 0.0, 0.5, 1.0, 1.5 and 2.0 wt%) of the nanoscale carbon fillers are considered. The addition of CNFs, GNPs or hybrid combinations of CNFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Herein, it depends on obtaining uniform dispersion of GnPs and CNTs in the sizing solvent, if researchers want to successfully achieve the multifunctional CFRP composites. As the more recently reported, the addition of different geometric shapes nanoparticles could be an effective way to achieve homogeneous dispersion [37,38]. The composites modified by hybrids nanoparticles have achieved better interfacial, mechanical, electrical and thermal properties [39].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Herein, it depends on obtaining uniform dispersion of GnPs and CNTs in the sizing solvent, if researchers want to successfully achieve the multifunctional CFRP composites. As the more recently reported, the addition of different geometric shapes nanoparticles could be an effective way to achieve homogeneous dispersion [37,38]. The composites modified by hybrids nanoparticles have achieved better interfacial, mechanical, electrical and thermal properties [39].…”
Section: Introductionmentioning
confidence: 85%
“…It was reported that the long and flexible 1D nanoparticles bridged adjacent 2D nanoparticles and inhibited their aggregation, leading to an improvement of contact surface area between hybrid nanoparticles structures and the polymer [40]. A synergetic effect in terms of fracture energy and fatigue [37], tensile strength and elastic modulus [41] were reported in carbon nanofibers (CNF) and GnP hybrid nanoparticles composites. Better mechanical and thermal properties were reported in epoxy composites with 0.9 wt.% multi-graphene platelets (MGP) and 0.1 wt.% CNTs due to a more efficient network formation [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smallest GO sheet size shows maximum enhancement in fracture toughness [80]. Recently, Ladani et al [81] studied the effect of reinforcement of 1-D Carbon Nanofibres or 2-D graphene nanoplatelets or hybrid combinations of 1-D Carbon nanofibres and 2-D graphene nanoplatelets. The nanoscale carbon fillers were dispersed by (0.0, 0.5, 1, 1.5 and 2 wt%) to observe the effects of the dimensional shape and concentration.…”
Section: Graphenes (Graphene-based Modified Epoxy Nanocomposites)mentioning
confidence: 99%
“…This disadvantage limits its application in high‐technology fields. Many techniques have been successfully employed to enhance the fracture toughness of EP …”
Section: Introductionmentioning
confidence: 99%